К изучению фауны совок Крыма. I. Подсемейство Hadeninae (Noctuidae, Lepidoptera) - Ключко, З.Ф. (Вестник зоологии, 1967)
At present 64 species of the screech owl of subfamily Hademinae are registered in Crimea, including 46 species firstly observed in the Crimean fauna and 3 — in the Ukrainian one. The Eurasian species are prevailing, and a considerable group is represented by ponto-mediterranean species of the mentioned subfamily.